The Impact of Coronavirus Disease 2019 on Pregnant Women is Multifaceted [Letter] - Wang B; Lv X; Huang J (Dove Medical Press, 2024)
Biaobiao Wang,* Xiuqing Lv,* Jingrui Huang Department of Obstetrics, Xiangya Hospital Central South University, Changsha, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingrui Huang, Department of Obstetrics, Xiangya Hospital Central South University, 87 Xiangya Road, Changsha, 410008, People’s Republic of China, Email jingruihuang@hotmail.com; huangjingrui@csu.edu.cn